KRÓL-DUCH JULIUSZA SŁOWACKIEGO W RECEPCJI JAROSŁAWA IWASZKIEWICZA - Gędas, Katarzyna (Colloquia Litteraria, 2016)
he article addresses instances of the reception of Juliusz Słowacki’s Król- -Duch in Jarosław Iwaszkiewicz’s life and works; it is based on Iwaszkiewicz’s memoirs, diaries, reviews, literary texts, correspondence with his wife Anna, and the marginalia left on the copies of Król-Duch remaining in the poet’s archive in Podkowa Leśna. The article also includes a critical edition of the three texts on Król-Duch by Iwaszkiewicz, published in “Wiadomości Literackie” in 1924, 1925, and 1927. The first two texts critically review Słowacki’s narrative poem, the third is a literary sketch putting Król-Duch side by side with Marcel Proust’s In Search of Lost Time.